Seed yam production from presprouted minisetts with varied thickness of storage parenchyma - Aighewi, B.A.; Akoroda, M.O.; Asiedu, Robert (2003)
A large proportion of harvested yams (Dioscorea rotundata) is used as planting material and contribute immensely to the overall cost of production. Four thicknesses (5,10,15, and 30-40 mm) of minisetts of two yam varieties were pre-sprouted in shredded coir and grown in the field to determine their suitability for producing seed yams. Variety Abi had a better sprouting ability, and more plants survived at harvest than variety Pepa. The number of sprouts/sett was highest for the thinnest (5 mm) setts. The percentage of plantsthat survived till harvest was significantly higher for the 5 mm-thick setts than 30-40mm-thick setts. In 1995, there were only slight differences among the thicknesses in totalseed yam yields. Abi produced more seed yams which weighed <400 g, while Pepayielded more tubers >400 g. Only in 1995 did the 10, 15 and 30-40 mm-thick setts yieldremarkably more tubers of 800-1000 g as compared to the 5 mm-thick setts. With the 5mm-thick setts being comparable to the other thicknesses in the yield of seed yams of150-250 g, they could be utilized for seed yam production, while more of the storageparenchyma of the tubers is used for food.